Serum Magnesium Ion Content in 32-36 Weeks Preterm Labor Patients in Dr. Mohammad Hoesin Hospital Palembang - Shanti A. Diani (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To determine the average levels of serum magnesium in 32-36 weeks of preterm labor patients and to compare the average of serum level of magnesium serum in preterm delivery 32-36 weeks with an average content of magnesium ions in normal delivery. Methods: The study is an observational descriptive cross-cut design to determine level of magnesium serum at 32-36 weeks of preterm labor. Result: Samples of this study were patients with preterm labor who were treated at the Department of Obstetrics and Gynecology in Dr. Mohammad Hoesin Palembang from January 1st, 2009 until July 31st, 2010. The number of samples was 33 subjects. Most subjects were in the range of 20-35 years of age. The largest parity in the preterm group was 0, namely 14 subjects (42.5%), while in the normal pregnancy group it was 1, viz. 12 subjects (36.4%). Conclusion: Based on the results of studies, the magnesium levels of 32-36 weeks preterm labor group was lower than the normal delivery group. The average of magnesium level in preterm labor group was 1.57 Â± 0.18, while in the normal delivery group, it was 1.88 Â± 0.23. There was a statistically significant difference found on magnesium levels in both groups (p